İşletmelerde rekabet üstünlüğü yaratma açısından değer temelli pazarlamada ilişkisel pazarlamanın incelenmesi ve bir uygulama - Duman, Yaprak (My University, 2007)
yaklaşımlarında önemli değişimler meydana gelmiştir. Pazarlama çeşitli evrelerden geçerek şuan uygulanan farklı anlayışlara yerini bırakmıştır. Artık işletmeler farklı rekabetler içine girmişlerdir. Ürünlerde farklılaşmaya gidemeyen, her yeni gün pazara bir çok firmanın dahil olduğu, tatmin seviyesinin çok yukarılarda olan müşteri kitlesinin artması firmalara, fark yaratmak için başka çözüm yolları aramaları gerektiğini fark ettirdi. Bunlardan dolayı da kendini pazarda diğer firmalardan ayıran kurumlar stratejilerinde değişiklikler yapmaya başladılar. Bu bağlamda değer temelli pazarlama ve ilişkisel pazarlama kavramı kurumlara pazardaki yerleri için farklı çözüm üretti. Firmalar hedeflerine, değer kavramını koyarken, onu nasıl tanımlayıp, nasıl yaratacaklarını ve müşterilere sunarken nasıl bir tarzda yaklaşacaklarını eklediler. Bunları yaparken de ilişkisel pazarlamayla ortak yürütülmesinin gerekli olduğunun farkına vardılar. Bu tezde değer temelli pazarlamanın ve ilişkisel pazarlamanın nasıl uygulandığı, firmaların müşterilerine yaklaşırken nasıl bir yol izlemeleri gerektiği, hangi stratejilerin önem kazandığını göstererek, uygulama kısmındaki sonuçlarla pekiştirilmiştir.

CAREFUL STUDY OF RELATIONSHIP MARKETING IN VALUE BASE MARKETING AND A CASE STUDY IN ORDER TO CREATE COMPETITION DOMINANCE IN BUSINESS There have been important changes in marketing approaches until it has been reached the current marketing applications. After having completed different stages and having passed through different channells, marketing has finally reached the current different marketing concepts. Comparies are in different competions. Those companies which never thought of variations among products, realized that they had to various solutions becouse search and find a lot of firms and companies were taking part in the market and the customer satisfaction level was getting higher and higher. Becouse of these reasons, the companies which seperated them selves from the others started making changes in their strategis. In this sense, companies created new solutions in the market for themselves using value based marketing and relational marketing technigues. Bay this way companies started putting value concepts in their targets. They also included in their policies how to define, how to create and how to present value concepts to their customers. While doing this, they realized that value based marketing and relationship marketing couldn’t be seperated from each other and had to be applied together.In this study, how value based marketing and relationship marketing could be applied by companies what kind of ways and techniques the campanies should follow while approaching their customers, what strategies have gaind importance. It has been supported by the data results in application about.
Keywords: Değer Temelli Pazarlama; İlişkisel Pazarlama; Pazarlama; Rekabet